Role of postmortem bioenergetics in beef colour chemistry - Ranjith Ramanathan; Morgan Denzer; Frank Kiyimba; Keayla Harr; Surendranath P. Suman; Melvin Hunt; Morgan Pfeiffer; Gretchen G. Mafi; Yuan H. Brad Kim (Italian Journal of Animal Science, 2023)
Meat colour is one of the primary factors affecting the acceptability of retail meat cuts. Therefore, displaying the natural bright-red colour of meat is a major goal of the meat industry. Consumers frequently reject to retail meat cuts with discolouration even at low levels of surface browning and/or darkening, which in turn results in significant food waste and economic loss. Thus, understanding the factors that influence meat colour deviations such as discolouration or darkening is crucial in developing effective strategies to minimise the display colour-related quality issues. Numerous factors influence series of biochemical reactions of post-mortem muscles and the chemical state of myoglobin, which ultimately affects meat colour and colour stability. Recent studies have demonstrated the incidence of dark-cutting beef post-mortem can be attributed to the combination of lower glycolytic potential, less glycolytic metabolites, enzymes and dysregulated energy metabolism. This review will focus on the role of post-mortem bioenergetics and mitochondria dynamics that affect beef colour chemistry.